(untitled) (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2026)
This article characterizes the nature and scope of the challenges that the expansion of authoritarian regimes since the beginning of the 21st century poses to international norms and institutions that seemed consolidated at the end of the last century. The changes that this expansion produces in international relations include rejections and ignorance of the bases of legitimacy of the international order. These are challenges that this study contextualizes, describes and analyzes by combining the political perspective of the Theories of International Relations with the regulations of International Law, to finally illustrate their manifestations with the positions and arguments of a selection of authoritarian regimes before the Universal Periodic Review of the Human Rights Council of the United Nations.